First-principles insight into the photoelectronic properties of Ge-based perovskites. Issue 90 (13th September 2016) - Lu, Xiaoqing; Zhao, Zigang; Li, Ke; Han, Zhaoxiang; Wei, Shuxian; Guo, Chen; Zhou, Sainan; Wu, Zhonghua; Guo, Wenyue; Wu, Chi-man Lawrence
Abstract : First-principles investigations were performed to elucidate the effects of A and X in Ge-based MAGeX3 perovskites (MA = CH3 NH3 + ; X = Cl −, Br −, and I − ) and AGeI3 (A = Cs +, CH3 NH3 +, HC(NH2 )2 +, CH3 C(NH2 )2 +, and C(NH2 )3 + ) on the photoelectronic properties. Abstract : The crystal configuration, electronic structure, charge-carrier transport, and optical properties of Ge-based MAGeX3 perovskites (MA = CH3 NH3 + ; X = Cl −, Br −, and I − ) and AGeI3 (A = Cs +, MA, FA (HC(NH2 )2 + ), MO (CH3 C(NH2 )2 + ), and GA (C(NH2 )3 + )) were investigated using first-principles theory. The results showed that the increase in Ge–X bonds (from Cl − to I − ) in MAGeX3 increased the volumes, weakened the covalent coupling of Ge–X, lowered the bandgaps, reduced the electron and hole effective masses, and red shifted the absorption spectra. Different A cations in the AGeI3 systems altered the package of perovskite crystals and thus significantly influenced the electronic and optical properties of those perovskites. Electronic property analyses revealed that the valence band maxima (VBM) of AGeI3 perovskites were mainly contributed by the I 5p and Ge 4s orbitals, whereas the conduction band minima (CBM) were dominated by Ge 4p orbitals. In AGeI3 perovskites, the bandgap increased and the absorption spectrum blue shifted in the sequence of Cs + → MA → FA → MO → GA. Our results highlighted the effects of A and X on the photoelectronic properties of Ge-based perovskites.